2020
DOI: 10.1002/ange.202003282
|View full text |Cite
|
Sign up to set email alerts
|

A Cationic Oligomer as an Organic Template for Direct Synthesis of Aluminosilicate ITH Zeolite

Abstract: There are a large number of zeolites, such as ITH, that cannot be prepared in the aluminosilicate form. Now, the successful synthesis of aluminosilicate ITH zeolite using a simple cationic oligomer as an organic template is presented. Key to the success is that the cationic oligomer has a strong complexation ability with aluminum species combined with a structural directing ability for the ITH structure similar to that of the conventional organic template. The aluminosilicate ITH zeolite has very high crystall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…1,27 Rollmann et al 28 were the rst to use 1,4-diazabicyclo[2.2.2] octane-1,4-dibromobutane polymer as OSDA to generate GME and MOR zeolites, which was lately also used to fabricate MTW zeolite. 29 More recently, Xiao et al reported the sole use of polydiallyldimethylammonium chloride as OSDA to crystallize *BEA zeolite with hierarchical porosity, 21 and the use of a simple oligomer ( 30 Additionally, polycations are also useful porogens in fabricating hierarchically porous zeolites, i.e., zeolites with integrated macro-/meso-porosity. 31,32 Aer the combustive removal of these polycation porogens, interconnected mesopores that are benecial to mass transport can be generated because pore-connectivity has been recognized as a crucial factor for the diffusion process.…”
Section: Introductionmentioning
confidence: 99%
“…1,27 Rollmann et al 28 were the rst to use 1,4-diazabicyclo[2.2.2] octane-1,4-dibromobutane polymer as OSDA to generate GME and MOR zeolites, which was lately also used to fabricate MTW zeolite. 29 More recently, Xiao et al reported the sole use of polydiallyldimethylammonium chloride as OSDA to crystallize *BEA zeolite with hierarchical porosity, 21 and the use of a simple oligomer ( 30 Additionally, polycations are also useful porogens in fabricating hierarchically porous zeolites, i.e., zeolites with integrated macro-/meso-porosity. 31,32 Aer the combustive removal of these polycation porogens, interconnected mesopores that are benecial to mass transport can be generated because pore-connectivity has been recognized as a crucial factor for the diffusion process.…”
Section: Introductionmentioning
confidence: 99%